SUPERKIMBERLITES: A GEODYNAMIC DIAMOND WINDOW TO THE EARTHS CORE - Haggerty S.E. (My University, 1994)
Carbon is the fourth most abundant element in the solar system. In the Earth carbon is in atmospheric CO2, limestone, other organic products, graphite and trace diamond; interstellar diamond, however, is ubiquitous. Diamond is well known for some unique physical and chemical properties, but it is perhaps less well known that the mineral is geologically ancient (3.3 Ga), that its origins are deep in the mantle (> 180 km), and that diamonds are among the deepest solid objects to reach the surface of the Earth; rare diamonds are from the transition zone (400–670 km), and other diamonds possibly nucleated in the lower mantle (> 670 km). Transport to the surface is in volatile (COHNS)-charged highly explosive kimberlite and lamproite volcanoes. These volcanoes are sited exclusively in the oldest (> 1.7 Ga), tectonically most stable, and thickest (∼ 200 km) regions of crust and upper mantle lithosphere. The energetics required for volcanism are so exceptional and the sources so deep that possible connections between and among the core, geomagnetism, plumes and diamonds are explored. Some correlations are established and others are implied. The results are sufficiently enticing to propose that kimberlites and geographically and temporally associated carbonatites are continental recorders of plumes dating back to at least 2.8 Ga, and that some diamonds may have recorded core events dating back to 3.3 Ga, or possibly earlier.